Pulmonary hypertension: prevalence and mortality in the Armadale echocardiography cohort. Issue 24 (3rd July 2012) - Strange, Geoff; Playford, David; Stewart, Simon; Deague, Jenny A; Nelson, Helen; Kent, Aaron; Gabbay, Eli
Abstract : Background: Pulmonary hypertension (PHT) lacks community prevalence and outcome data. Objective: To characterise minimum 'indicative' prevalences and mortality data for all forms of PHT in a selected population with an elevated estimated pulmonary artery systolic pressure (ePASP) on echocardiography. Design: Observational cohort study. Setting: Residents of Armadale and the surrounding region in Western Australia (population 165 450) referred to our unit for transthoracic echocardiography between January 2003 and December 2009. Results: Overall, 10 314 individuals (6.2% of the surrounding population) had 15 633 echo studies performed. Of these, 3320 patients (32%) had insufficient TR to ePASP and 936 individuals (9.1%, 95% CI 8.6% to 9.7%) had PHT, defined as, ePASP>40 mm Hg. The minimum 'indicative' prevalence for all forms of PHT is 326 cases/100 000 inhabitants of the local population, with left heart disease-associated PHT being the commonest cause (250 cases/100 000). 15 cases of pulmonary arterial hypertension/100 000 inhabitants were identified and an additional 144 individuals (15%) with no identified cause for their PHT. The mean time to death for those with ePASP >40 mm Hg, calculated from the first recorded ePASP, was 4.1 years (95% CI 3.9 to 4.3). PHT increased mortality whatever the underlying cause, but patients with PHT from left heart disease had the worst prognosis and those with idiopathic pulmonary arterial hypertension receiving disease-specific treatment the best prognosis. Risk of death increased with PHT severity: severe pulmonary hypertension shortened the lifespan by an average of 1.1 years compared with mild pulmonary hypertension. Conclusions: In this cohort, PHT was common and deadly. Left heart disease was the most common cause and had the worst prognosis and treated pulmonary arterial hypertension had the best prognosis.